Perioperative neurocognition in elderly patients. Issue 1 (February 2018) - Fu, Huiqun; Fan, Long; Wang, Tianlong
Abstract : Purpose of review: The extrinsic risk factors for postoperative cognitive disturbance have been a source of concern during the perioperative period, and these risk factors remain the subject of controversy. This review of recent studies focuses on the effect of these factors on postoperative cognitive disturbance during the perioperative period. Recent findings: Impairment of cerebral autoregulation may predispose patients to intraoperative cerebral malperfusion, which may subsequently induce postoperative cognitive disturbance. The neurotoxicity of several volatile anesthetics may contribute to cognitive functional decline, and the impact of intravenous anesthesia on cognitive function requires further exploration. Multimodal analgesia may not outperform traditional postoperative analgesia in preventing postoperative delirium. Furthermore, acute pain and chronic pain may exacerbate the cognitive functional decline of patients with preexisting cognitive impairment. The nuclear factor-kappa beta pathway is an important node in the neuroinflammatory network. Summary: Several intraoperative factors are associated with postoperative cognitive disturbance. However, if these factors are optimized in perioperative management, postoperative cognitive disturbance will improve.